Studies of Phase Transformation Kinetics in the System of Nanocrystalline Iron/Ammonia/Hydrogen at the Temperature of 350 °C by Means of Magnetic Permeability In Situ Measurement - Walerian Arabczyk; Rafał Pelka; Agnieszka Brzoza-Kos; Ireneusz Kocemba; Paulina Rokicka-Konieczna; Katarzyna Skulmowska-Polok; Kamila Klimza; Zofia Lendzion-Bieluń (Applied Sciences)
The kinetics of phase transformations in the nitriding process α-Fe → γ’-Fe4N → ε-Fe3-2N of the pre-reduced iron ammonia synthesis catalyst was investigated under in situ conditions (atmospheric pressure, 350 °C) by measuring changes of mass, gas phase composition, and magnetic permeability in a differential tubular reactor. The iron nanocrystallite size distribution according to their specific active surface areas was measured, and it was found that the catalyst is bimodal as the sum of two Gaussian distributions, also differing in the value of the relative magnetic permeability. Relative magnetic permeability of small α-Fe crystals in relation to large crystals is higher by 0.02. In the area of α → γ’ transformation, the magnetic permeability dependencies change, proving the existence of two mechanisms of the α-Fe structure change in the α-Fe → γ’-Fe4N transformation. In the first area, a solution of α-Fe (N) is formed with a continuous and insignificant change of the crystal lattice parameters of the iron lattice. In the second area, there is a step, oscillatory change in the parameters of the iron crystal lattice in FexN (x = 0.15, 0.20, 0.25 mol/mol). In the range of γ’-Fe4N → ε-Fe3-2N transformation, a solution is formed, with nitrogen concentration varying from 0.25–0.45 mol/mol. During the final stage of the nitriding process, at a constant value of the relative magnetic permeability, only the concentration of nitrogen in the solution εr increases. The rate of the phenomenon studied is limited by a diffusion rate through the top layer of atoms on the surface of iron nanocrystallite. The estimated value of the nitrogen diffusion coefficient varied exponentially with the degree of nitriding. In the area of the solution, the diffusion coefficient is approximately constant and amounts to 5 nm2/s. In the area of oscillatory changes, the average diffusion coefficient changes in the range of 3–11 nm2/s, and is inversely proportional to the nitrogen content degree. The advantage of the research method proposed in this paper is the possibility of simultaneously recording, under reaction conditions, changes in the values of several process parameters necessary to describe the process. The research results obtained in this way can be used to develop such fields of knowledge as heterogeneous catalysis, materials engineering, sensorics, etc.